STUDI KESIAPSIAGAAN BENCANA PELAKU USAHA TERHADAP POTENSI LETUSAN GUNUNG GUNTUR DI KAWASAN WISATA CIPANAS, KABUPATEN GARUT - Isabella Wibowo, Averina
Cipanas Area is a tourism area with a hot spring as the main attraction. This tourism area is developing at the hillside Guntur Volcano and is located 5km away from the peak. Guntur Volcano could be activated whenever and produce a huge eruption that will affect the surrounding areas. Disaster preparedness is important to increase the Cipanas area’s capacity to face a potential disaster. This study is done with identifying the development that is happening in the Cipanas area to confirm the vulnerability that exists in this area towards the potential eruption of Guntur Volcano. To decrease the vulnerability that appears with the development of Cipanas, capacity building is needed, one of them is disaster preparedness of business actors because tourism development that is happening in the Cipanas area. Area and tourism development can be seen from the land cover change, increased number of hotels, and the high number of tourists. Disaster preparedness of business actors is still low because of the low knowledge of potential disaster. Business actors also don’t have emergency disaster planning and basic accommodation that is needed and don’t understand how to do evacuation correctly. But, the early warning system goes well.